Adapting crops for climate change: regaining lost abiotic stress tolerance in crops - Palmgren, Michael; Shabala, Sergey (Frontiers in Science, 2024)
It is often stated that agricultural outputs need to increase substantially to meet the demands for more food posed by a growing population. However, when accounting for climate change, we argue that current projected increases are unrealistic and a more realistic goal would be to maintain yields per area of food production. This will require breeding for crops with increased tolerance to abiotic stresses such as drought, salinity, waterlogging, and high temperatures. This goal can be accomplished in one of two ways: by introducing stress tolerance genes into present high-yielding crops or by increasing the yields of already tolerant orphan crops and/or wild plants. We argue that the first strategy will require easing the restrictions on the use of gene editing technologies and making substantial improvements to cell-based phenotyping to identify the stress tolerance genes available in the gene pool of a crop and its wild relatives. The success of the second strategy will depend on the number of domestication genes that need to be selected for in order to obtain yields comparable to present-day cultivars. It is still too early to conclude which of the two strategies, rewilding (bringing genes lost from wild ancestors back to domesticated crops) or de novo domestication (domesticating resilient wild plants or underutilized crops directly), will be most effective for future sustainable agriculture. However, given the importance of the issue, some rapid action needs to be taken.